2007
DOI: 10.1044/1092-4388(2007/015)
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Nonword Repetition Performance of Children With and Without Specific Language Impairment: A Meta-Analysis

Abstract: These findings have potential to affect how nonword repetition tasks are used and interpreted, and suggest several directions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
248
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(275 citation statements)
references
References 62 publications
(165 reference statements)
20
248
1
6
Order By: Relevance
“…The choice of tasks was largely driven by the literature on language impairments (LI), both congenital and acquired. Children with LIwho tend to fare poorly on tasks of non-word repetition (Graf-Estes et al, 2007) -are also apt to show impairments in a range of other skills (Bishop, 2006). For instance, children with LI show differences from typically developing children in their speed of processing and motor response latency (Miller et al, 2001;Schul et al, 2004), attentional resource capacity/allocation (Marton et al, 2007;Finneran et al, 2009;Montgomery et al, 2008) and auditory or phonemic discrimination and processing (Bishop, 2006;Fox et al, 2011, cf.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of tasks was largely driven by the literature on language impairments (LI), both congenital and acquired. Children with LIwho tend to fare poorly on tasks of non-word repetition (Graf-Estes et al, 2007) -are also apt to show impairments in a range of other skills (Bishop, 2006). For instance, children with LI show differences from typically developing children in their speed of processing and motor response latency (Miller et al, 2001;Schul et al, 2004), attentional resource capacity/allocation (Marton et al, 2007;Finneran et al, 2009;Montgomery et al, 2008) and auditory or phonemic discrimination and processing (Bishop, 2006;Fox et al, 2011, cf.…”
Section: The Present Studymentioning
confidence: 99%
“…NWR tasks have been used with many clinical populations (Gathercole, 2006;Bishop et al, 2006;Conti-Ramsden et al, 2001;Grant et al, 1997;Laws & Gunn, 2004;Graf-Estes et al, 2007) and across languages (Sahlen et al, 1999;reviewed in Coady & Evans, 2008). However, there is no current consensus about which underlying skills, including sensorimotor skills, contribute to NWR performance, and in what proportion (Coady & Evans, 2008;Snowling et al, 1981Snowling et al, , 1986.…”
Section: Articulating Novel Words: Children's Oromotor Skills Predictmentioning
confidence: 99%
“…Children with SLI are typically able to repeat short nonwords accurately; however, their performance decays with nonwords of three or more syllables, suggesting that the difficulty is in holding novel phonological material in memory, rather than in basic aspects of perception and production. Previous studies have suggested that around three-quarters of children with SLI have considerable difficulties with nonword repetition (Conti-Ramsden, Botting, & Faragher, 2001; also see meta-analysis by Graf-Estes, Evans, & Else-Quest, 2007).…”
mentioning
confidence: 99%
“…A meta-analysis by Graf-Estes, Evans and Else-Quest (2007) showed that the effect of LI, which should be maximized for optimal clinical value, is influenced by item properties such as syllable length and wordlikeness or phonotactic probability. Children with LI appear to perform weakly across all nonword lengths, but show greater difficulty with longer items (e.g.…”
Section: Manipulating Properties Of Nwrtsmentioning
confidence: 99%